The subglacial geology of Wilkes Land, East Antarctica. Issue 7 (14th April 2014) - Aitken, A. R. A.; Young, D. A.; Ferraccioli, F.; Betts, P. G.; Greenbaum, J. S.; Richter, T. G.; Roberts, J. L.; Blankenship, D. D.; Siegert, M. J.
Abstract: Wilkes Land is a key region for studying the configuration of Gondwana and for appreciating the role of tectonic boundary conditions on East Antarctic Ice Sheet (EAIS) behavior. Despite this importance, it remains one of the largest regions on Earth where we lack a basic knowledge of geology. New magnetic, gravity, and subglacial topography data allow the region's first comprehensive geological interpretation. We map lithospheric domains and their bounding faults, including the suture between Indo‐Antarctica and Australo‐Antarctica. Furthermore, we image subglacial sedimentary basins, including the Aurora and Knox Subglacial Basins and the previously unknown Sabrina Subglacial Basin. Commonality of structure in magnetic, gravity, and topography data suggest that pre‐EAIS tectonic features are a primary control on subglacial topography. The preservation of this relationship after glaciation suggests that these tectonic features provide topographic and basal boundary conditions that have strongly influenced the structure and evolution of the EAIS. Key Points: Wilkes Land geology is comprehensively characterized for the first time New and known continent‐scale faults and sedimentary basins are defined These major tectonic features define current subglacial topography